2022
DOI: 10.21037/qims-21-290
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between drug-sensitive and drug-resistant tuberculosis with machine learning for clinical and radiological features

Abstract: Background: Tuberculosis (TB) drug resistance is a worldwide public health problem that threatens progress made in TB care and control. Early detection of drug resistance is important for disease control, with discrimination between drug-resistant TB (DR-TB) and drug-sensitive TB (DS-TB) still being an open problem. The objective of this work is to investigate the relevance of readily available clinical data and data derived from chest X-rays (CXRs) in DR-TB prediction and to investigate the possibility of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…In these examples, it can be seen that for the DR-TB class, activations are more frequent. This is consistent with previous results [ 9 ], where DR-TB patients are shown to have more abnormalities in their lungs.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In these examples, it can be seen that for the DR-TB class, activations are more frequent. This is consistent with previous results [ 9 ], where DR-TB patients are shown to have more abnormalities in their lungs.…”
Section: Resultssupporting
confidence: 94%
“…This study observed that the co-existence of multiple findings (multiple cavities, thick-walled cavities, disseminated lesions along the bronchi, whole-lung involvement) was indicative of DR-TB. Finally, more recent work [ 9 ] compared 1455 DR-TB and 782 DS-TB cases, using two clinical features and 23 types of radiological findings. A support vector machine was used to distinguish between DR-TB and DS-TB with an AUC of 0.78.…”
Section: Previous Workmentioning
confidence: 99%
“…Additionally, this study revealed that a retreated history and a longer period of previous anti-TB treatment were more common in patients with MDR-PTB than in those with DS-PTB, which corroborates some previous studies. [8][9][10][11][12] Anti-TB treatment times, adverse reactions, and interrupted or failed treatment have been reported many times as risk factors of MDR-PTB, which inevitably prolong the treatment period. Moreover, our results showed that CD4 + T and CD4/CD8 + T lymphocyte count ratio was lower in patients with MDR-PTB than in those with DS-PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 demonstrates the GradCAM heatmap [ 66 , 67 , 68 ] of various drug-resistant types. We divide the entire lung into six parts: left and right at the top, center left and right, and bottom left and right.…”
Section: Discussionmentioning
confidence: 99%